The Roles of Dive Centers in Conserving Coral Reefs to Support Tourism Industry in Gili Trawangan - I Gusti Ngurah Paulus Widya Eka Saputra (Gadjah Mada Journal of Tourism Studies, 2019)
Gili Trawangan is a popular tourism destination among scuba divers and snorkelers. It is renowned for its diverse coral reefs and marine life. However, the rapid growth of the tourism industry has a degrading impact on the condition of coral reefs. It is recorded that 25 dive centres are operating on the island. As one of the primary tourism stakeholders, the dive centre has a vital role in conserving coral reefs to support the tourism industry, to protect coral reefs as a natural resource and tourism attraction. This research has two objectives—identifying the roles of the dive centres in coral reef conservation and emphasising their focuses in supporting the tourism industry in Gili Trawangan through conservation programs. This study is qualitative research, conducted at five dive centres in Gili Trawangan. This research reveals that the five dive centres have been carrying out numerous roles in conserving coral reefs in order to support the tourism industry on the island. Moreover, each of the dive centres has various and different outcome focuses on programs they implement. Dive centres in Gili Trawangan have established a partnership with other stakeholders in order to ease implementation of their programs and to involve as many parties in conserving coral reefs.